Motion and muscle activity of synchronized rolling-type double-leg circles on a pommel horse - Nawa, M.; Yamada, A.; Nishiwaki, K.; Yamawaki, K.; Ikegami, Y.; Nakamura, Y.; Yamasaki, T. (Proceedings, 2020)
Experimental analyses of motions of a double-leg circle were conducted for a smooth and dynamic movement. A motion capture system provided the data for two different gymnasts; one is well trained and the other has an average skill level. Lissajous analysis was done for a tip-toe circling motion and a rolling motion around a longitudinal axis of a body. The results show that synchronization between the tip-toe circling and the body-rolling around the body`s longitudinal axis is crucial. Muscle activity was also analyzed from electromyogram data when the gymnasts performed double-leg circles, and the muscle activity characteristics of synchronized rolling-type circles were uncovered.